Social Support, Age and Borderline Personality - Christin Wibhowo; Sofia Retnowati; Nida Ul Hasanat (Universitas Katolik Soegijapranata, 2018)
This study is aimed 1).to find out relation among the social support and BP. 2).Totest the difference BP based on age. The hypothesis in this study is1). there is a relationship between social support and BP. 2). There is difference BP on based age. All data are measured with scales. The partisipans to this study amounted to 247 adults aged 20-40 years. The data obtained are analyzed with SPSS program. The result showed that 1).There is norelationship between social support and BP (r= -0,40; p= 0,182) 2).There is no difference BP on based age (F= 1,491;p=0,097).Methodological recommendations are as follows 1)pay attention to sources and types of social support 2).analyze the profile of trains in each age group and gender.